A COMPREHENSIVE REVIEW ON THE NON-DESTRUCTIVE TEST FOR POLYMER MATRIX COMPOSITE - Wahjudi, Ari; Widodo, Agung Sugeng (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Polymer matrix composite (PMC) is widely applied in structural engineering mainly due to its high strength-to-weight ratio. Of many benefits, the transportation industry uses this type of material mainly due to its high strength-to-weight ratio. In many cases, this strength-to-weight ratio is higher than aluminum or steel base materials. Its manufacturing and fabrication, however, are challenging. For this reason, destructive and non-destructive tests to control product quality during the manufacturing process are worked out. The non-destructive test delivers many benefits since the finished product does not. This paper discusses the benefits of polymer matrix composite application in the structural engineering. In addition, this work also outlined the key parameters and comparison of various non-destructive tests applied for the PMC.